2009
DOI: 10.1007/s11626-009-9250-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of various antioxidants on the development of parthenogenetic porcine embryos

Abstract: The major objective of this study was to improve the development rate of parthenogenetic porcine embryos. In this study, the anti-oxidative and anti-apoptotic effects of three antioxidants, β-mercaptoethanol (β-ME), α-tocopherol, and extracellular superoxide dismutase (EC-SOD), were examined on the development of parthenogenetic porcine embryos. The development rate of parthenogenetic porcine embryos to the blastocyst stage was 8.1% for control; 19.1%, 14.6%, and 5.0% for 1, 3, and 5 μM β-ME; 17.2% and 17.5% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Recent studies have indicated the effects of antioxidants on the development of parthenogenetic porcine embryos. Antioxidants increase the average number of total cells at the blastocyst [55]. However, in this study no difference was detected between the P. bracteatum and the control group in the rate and developmental competence of oocytes obtained through IVF.…”
Section: Discussioncontrasting
confidence: 79%
“…Recent studies have indicated the effects of antioxidants on the development of parthenogenetic porcine embryos. Antioxidants increase the average number of total cells at the blastocyst [55]. However, in this study no difference was detected between the P. bracteatum and the control group in the rate and developmental competence of oocytes obtained through IVF.…”
Section: Discussioncontrasting
confidence: 79%
“…Treatment with pGM-CSF in the IVC medium also improved the developmental potential of porcine IVF embryos (28). In addition, the supplementation of IVC medium with β-ME was able to increase the developmental competence of porcine PA embryos (29). β-ME was also able to increase intracellular glutathione levels and reduce damage to the embryo caused by ROS, thus improving embryo development.…”
Section: Discussionmentioning
confidence: 88%
“…Usually, supplementation of embryo culture media with antioxidants is associated not only with improvements in embryo production rates, but also with enhancing embryo quality 12 , 33 . In our study, the increased blastocyst rates observed after supplementation with 10 µM NMPG were not associated with an improvement in embryonic quality in terms of TCN or the ICM/TE ratio.…”
Section: Discussionmentioning
confidence: 99%